Factors Influencing University Students’ User Satisfaction and Continuous Intention to Use Short Video Apps for Learning in Beijing, China - Gao, Mingming (Scholar: Human Sciences, 2025)
Purpose: This article aimed to research the factors influencing University Students’ user satisfaction and continuous intention to Use Short Video App for Learning in Beijing, China. The conceptual framework presented cause-and-effect relationships between product originality, satisfaction, product demonstrability, privacy protection behavior, new product novelty, continuous intention to use, and information social influence. Research design, data, and methodology: The researcher adopted a quantitative technique (n=500) to administer the questionnaire to students in Beijing, China. The researcher employed non-probability sampling methods, including judgmental sampling for selecting three schools, quota sampling to determine the sample size, and convenience sampling for data collection and distribution of questionnaires both online and offline. Data analysis was conducted using structural equation modeling (SEM) and confirmatory factor analysis (CFA) to assess model fit, reliability, and construct validity. Results: The uniqueness of a product has a considerable effect on users’ satisfaction. The ability to demonstrate a product has a notable impact on user satisfaction. Behaviors that protect privacy have a significant influence on user satisfaction. The innovation of new products has a substantial impact on user satisfaction. Satisfaction plays an important role in the intention to continue using. Normative social influence has a significant effect on the intention to continue using. Conclusions: This study suggested that to make BiliBili more effective, policymakers and programmed operators could increase product originality, product demonstrability, privacy protection behavior, new product novelty, and information social influence.